ASSOCIATION OF COMMUNITY BEHAVIOR AND CONDITION OF THE HOME EXPOSED TO VOLCANIC ASH WITH THE ACUTE RESPIRATORY INFECTION (ARI) AMONG VILLAGERS IN PERBAJI - Tarigan, Frida Lina (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Volcanic dust from the eruption of Mount Sinabung causes the air condition to be bad and also disturbs the health of the surrounding population. This causes the occurrence of Acute Respiratory Infection (ARI), as well as various other diseases such as cough, runny nose, sneezing, sore throat. The purpose of this study is to determine the relationship between citizen behavior and the condition of the house exposed to volcanic ash with the incidence of ARI (Acute Respiratory Infection) to the residents of Karo Regency Perbaji Village in 2017. Methods: This research is a cross-sectional study involved the head of family who is domiciled and has a permanent population of 209 households in the village of Perbaji, Tiganderket District, Karo Regency, with a total sample of 68 families. Data analysis used in this research is univariate and bivariate analysis with Chi Square test. Results: The result shows that based on Chi Square test, there is a significant correlation between residentsâ behavior exposed to volcanic ash with the incidence of ARI (p value = 0.000). It is noted also a significant correlation between the house condition exposed to volcanic ash and the ARI occurrence (p value = 0.000). Conclusion: The results suggested that the villagers of Perbaji Village to use masks if they are outdoors in the event of an eruption. For the poor housing conditions, it is expected that the residents will improve their houses, such as covering the holes that can be penetrated by volcanic ash using plastic or paper. It is needed to pay attention to the condition of Perbaji village residents who are exposed to volcanic ash by distributing masks, and giving free treatment.Â